Effect of environmental factor on some litter traits of sows in the tropics Mexican - Jesús Ek M. (Revista MVZ Cordoba, 2015)
Objective. To determine the effect of environmental factors on litter traits at birth and weaning, and their repeatabilities in four farms in the sub-humid tropics of Mexico. Materials and methods. Data from 46.249 to 50.316 litters for litter size at birth (LSB), number of piglets born alive (NBA), litter weight at birth (LWB), number of piglets weaned (NPW) and litter weight at weaning (LWW) were used. The statistical model for LSB, NBA and LWB included the effects of farm, farrowing year, farrowing season, parity number, simple interactions, random effects of sow and the error term. NPW and LWW were analyzed using the previous model plus the linear and quadratic effects of lactation length (LL). Results. The means for LSB, NBA, LWB, NPW and LWW were 11.7 piglets, 11.0 piglets, 16.1 kg, 10.3 piglets and 61.3 kg, respectively. All effects in the model affected the litter traits. Farrowing year x season interaction was significant for NPW, LWB and LWW. The dry season had the highest LSB, NBA y NPW. First parity sows had higher LSB and NBA means than for second parity sows. Parity increase until parity 4 to decrease thereafter. LL had a quadratic effect on NPW and LWW. Repeatability estimates for LSB, NBA, and LWB were 0.12, 0.12 and 0.14, respectively. Conclusions. All traits studied were influenced by the environmental factors studied. Repeatabilities for LSB, NBA and LWB were low.